State And Family Partnership In The Management Of Preschool Education In Japan And South Korea - Yakubova, Dilnoza Zokirjonovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This thesis analyzes the formation and effectiveness of state and family cooperation in the management system of preschool education in Japan and South Korea. During the study, the coverage of preschool education, parental participation, state policy and management mechanisms were studied based on data from the Ministries of Education of the two countries and international organizations (OECD, UNESCO). According to the results of the analysis, the high level of quality of education in Japan and South Korea is directly related to the financial support of the state and the active participation of the family. This experience is of urgent importance for Uzbekistan in the process of modernization of preschool education.